?OESOPHAGOSTOMIASIS IN BLACK BENGAL GOATS IN BANGLADESH (Biological Sciences - PJSIR, 1996)
Examination of the intestinal tracts (both small and large) of 208 apparently healthy slaughtered Black Bengal goats from different parts of Bangladesh revealed Oesophagostomum columbianum infection in 185(88.94%) cases. In the presence of the parasites, nodular lesions weredetected in thewallof the intestines of 166(79.81%)goats. The mean worm burden (28.66) and the number of nodules (30.88) varied independently. Both worm burden and nodule formation were found to be very much agedependent (p0.05). Sex of the animals had significant bearing on nodule formation, more in male than in female goats (p